Perancangan Ulang Satuan Pendidikan Nonformal (spnf) Sanggar Kegiatan Belajar (skb) Kabupaten Ciamis Dengan Pendekatan Aktivitas - Mega Az Zahra, Ranti; Akhmadi; Haristianti, Vika (eProceedings of Art & Design, 2024)
Non-formal education through Sanggar Learning Activities (SKB) has become one of the strategic alternatives in an effort to improve the School Average Age Index (RLS) in Indonesia. In support of such improvements, the SKB building must continue to operate, in order to facilitate communities that are not served by the formal education system. The research aims to develop an optimal interior design of the Sanggar Learning Activity, taking into account the functionality, aesthetics, and comfort aspects of its users. The methods used to gather primary data are with interviews, observations, and field studies, while secondary data is done with literary studies. Given the number of programmes organized by the SKB, there is a high level of activity. So the theme applied is "Collaborative Learning Space" with the concept used is "Integrated School", this concept embodies the idea of providing a balanced and integrated space between academic activities and skills, with design elements that support both. Thus, with this redesign it is expected to create a more dynamic, interactive, and relevant learning environment for learners, as well as generate a positive impact in the development of non-formal education in society. Keywords : SPNF, studio learning activities, educational institutional, non-formal